METACOGNITIVE STRATEGIES OF UNDERGRADUATE AND POSTGRADUATE STUDENTS IN READING - Bria, Maria Gaudensi; Mbato, Concilianus Laos (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2019)
Metacognitive strategies are widely used by students in learning activities, often without them realizing it. In this article, the researchers aimed to observe postgraduate and undergraduate students metacognitive strategies in reading. Reading is a memory construction, it is essential for successes in the future. Students who are self-determined and motivated are successful readers. Metacognitive strategies of student teachers in reading maturity inspire students to integrate ideas with experiences into the transformation of actions. As reading maturity shapes character, it is identified to those who are independently and eagerly participates in the activity. It focuses on critical thinking and reflection. This assessment of metacognitive strategies in reading may offer an idea to be a good readers and teachers in the future. Using mixed method approach, particularly questionnaires and interviews, the data were collected using procedural statistic SPSS independent t-test in order to have the description of how the two groups applied metacognitive strategies in reading. The findings showed that both postgraduate and undergraduate students utilized metacognition strategies. However, postgraduate students demonstrated more metacognitive strategies and maturity in reading.